2010
DOI: 10.5012/bkcs.2010.31.04.941
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of Hydrogen Bond Interactions in Fluoroacetic Acid Dimer

Abstract: Ab initio and density functional theory methods have been employed to study all theoretically possible conformers of fluoroacetic acid. Molecular geometries and energetic of cis and trans monomers and cis dimers in gaseous phase have been obtained using HF, B3LYP and MP2 levels of theory, implementing 6-311++G(d,p) basis set. It was found that cis rotamers are more stable. In addition, it was found that in comparison with acetic acid the strength of hydrogen bonding in fluoroacetic acid decreased. The infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The prototype in this case is α-fluoroacetic acid. Chermahini et al , [ 172 ] found four local-energy-minimum structures for this molecule in the gas phase by ab initio and DFT calculations. All molecules show slightly distorted C S symmetry, thus the heavy atoms are almost co-planar.…”
Section: Conformational Equilibriamentioning
confidence: 99%
“…The prototype in this case is α-fluoroacetic acid. Chermahini et al , [ 172 ] found four local-energy-minimum structures for this molecule in the gas phase by ab initio and DFT calculations. All molecules show slightly distorted C S symmetry, thus the heavy atoms are almost co-planar.…”
Section: Conformational Equilibriamentioning
confidence: 99%
“…Therefore, bond path is an universal indicator of bonded interactions . Accordingly, QTAIM has become a method that has already been successfully applied to understand conventional hydrogen bonds, , C–H···O bonds, and dihydrogen bonds. , …”
Section: Introductionmentioning
confidence: 99%
“…To further quantitatively explore these hydrogen bonding and electrostatic interactions between substrate and DMF and/or DBU (DBU‐H + ), we performed natural bond orbital (NBO) second‐order perturbation interaction energy analysis for transition states TS 4‐5 , TS 8c‐9c , and TS 11c‐12c (Supporting Information Table S3). The calculated results suggest that the total stabilization energies amount to 28.87 (substrates and DBU‐H + ) and 2.81 kcal/mol (DMF and DBU‐H + ) in transition state TS 4‐5 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To further quantitatively explore these hydrogen bonding and electrostatic interactions between substrate and DMF and/ or DBU (DBU-H 1 ), we performed natural bond orbital (NBO) second-order perturbation interaction energy [28][29][30] analysis for transition states TS 4-5 , TS 8c-9c , and TS 11c-12c (Supporting Information Table S3). [4][5] , respectively.…”
mentioning
confidence: 99%